Revitalizing established Industrial Companies: State of the Art and Success Principles of Digital Corporate Incubators. - Hille, Matthias; Lederer, Matthias; Forster, Dominik (14. Internationale Tagung Wirtschaftsinformatik, 2019)
In order to compete with radical digital ideas, more and more large companies are founding corporate incubators. These small and agile companies are designed to accelerate disruptive innovation and transfer it to the parent company. However, it is obvious that the design and work in these newly established units are often efficient and the return of ideas cannot be effectively realized. This paper has collected a list of 131, partly non-public, incubators and evaluated them according to classic design parameters for companies (e.g., location, industry, etc.). In addition, success factors for digital corporate incubators (such as the design of the innovation process) were collected for deriving success principles.<br
Keywords: Corporate incubators; innovation management; start-up management; innovation lab; new business development